2018
DOI: 10.1097/md.0000000000013548
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the prognostic value of long non-coding RNA PVT1 for cancer patients

Abstract: Background:Plasmacytoma variant translocation 1 (PVT1) is reported to be dysregulated in various cancers. Therefore, this meta-analysis was performed to clarify its utility as a prognosis marker in malignant tumors.Methods:Electronic databases, including PubMed, OVID, Cochrane Library, and Web of Science databases, were retrieved from inception to December 16, 2017. Typically, hazard ratios (HRs) and corresponding 95% confidence intervals (CIs) were calculated, so as to explore the relationship between PVT1 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…PVT1 can promote the development of glioma cells through various mechanisms, resulting in a worse prognosis for patients with glioma and high PVT1 expression [18,161,162]. Multiple meta-analyses have also shown that PVT1 can be used as a new tumor biomarker and a predictor of poor prognosis in different cancers [163][164][165][166][167].…”
Section: Perspectivesmentioning
confidence: 99%
“…PVT1 can promote the development of glioma cells through various mechanisms, resulting in a worse prognosis for patients with glioma and high PVT1 expression [18,161,162]. Multiple meta-analyses have also shown that PVT1 can be used as a new tumor biomarker and a predictor of poor prognosis in different cancers [163][164][165][166][167].…”
Section: Perspectivesmentioning
confidence: 99%
“…The level of PVT1 expression was signi cantly increased in cancers. A meta-analysis on a total of 23 studies reported that high PVT1 expression levels correlated with poor overall survival, larger tumor size, distant metastasis, and some other risk factors in cancer patients (21). In addition, it is found to be up-regulated in atrial muscle tissues from atrial brillation patients (22), and the myocardial tissues of sepsis rats (23).…”
Section: Discussionmentioning
confidence: 99%